2020
DOI: 10.1177/1066896919900548
|View full text |Cite
|
Sign up to set email alerts
|

A Malignant Neoplasm From the Jejunum With aMALAT1-GLI1Fusion and 26-Year Survival History

Abstract: The transcription factor GLI1 is a critical effector of the sonic hedgehog pathway. Gene fusions that activate GLI1 have recently been reported in several tumor types including gastroblastoma, plexiform fibromyxoma, a subset of pericytomas, and other soft tissue tumors. These tumors arise in a wide variety of anatomical origins and have variable malignant potentials, morphologies, and immunohistochemistry profiles. In this case report, we describe a malignant tumor from the jejunum with a MALAT1-GLI1 gene fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 31 publications
(62 reference statements)
0
31
0
1
Order By: Relevance
“…Malignant epithelioid tumor with GLI1 rearrangement is a recently described epithelioid neoplasm of the soft tissue that harbors MALAT1–GLI1 fusion with a metastatic potential[ 65 ]. In the GI tract, only one case in the jejunum has been reported[ 10 ]. Later, Agaram et al [ 66 ] reported GLI1 gene amplifications in a subset of soft tissue tumors with similar morphology, even though these tumors showed broader morphologic spectrum and inconsistent immunohistochemistry.…”
Section: Differential Diagnosis: Molecular Mimicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant epithelioid tumor with GLI1 rearrangement is a recently described epithelioid neoplasm of the soft tissue that harbors MALAT1–GLI1 fusion with a metastatic potential[ 65 ]. In the GI tract, only one case in the jejunum has been reported[ 10 ]. Later, Agaram et al [ 66 ] reported GLI1 gene amplifications in a subset of soft tissue tumors with similar morphology, even though these tumors showed broader morphologic spectrum and inconsistent immunohistochemistry.…”
Section: Differential Diagnosis: Molecular Mimicsmentioning
confidence: 99%
“…While PF behaves in a benign manner, its histologic mimics such as GISTs, smooth muscle tumors and nerve sheath tumors show malignant potential[ 8 , 9 ]. Moreover, its molecular mimics, such as gastroblastoma and malignant epithelioid tumor with glioma-associated oncogene homologue 1 ( GLI1 ) rearrangement, need to be excluded especially when evaluating small samples and when the molecular profiling is included in the work-up[ 10 ]. Herein we provide a concise review of PF focusing on its histologic and molecular differential diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this genetic similarity to plexiform fibromyxoma, the differences in clinical behaviour and morphology support maintaining separate classification. There have also been reports of neoplasms with MALAT1 – GLI1 fusions occurring in the jejunum 50 and deep soft tissue 51 . Additionally, a tumour with biphasic morphology and immunohistochemical features similar to those of gastroblastoma was reported in the duodenum, raising the possibility that ‘gastroblastoma’ can involve extragastric sites 52 .…”
Section: Gastroblastomamentioning
confidence: 99%
“…Mesenchymal tumors harboring GLI1 gene fusions are a rare but distinctive group of recently described neoplasms whose clinicopathologic features are currently evolving. Various fusion partners to GLI1 have been described to date, including ACTB , MALAT1 , and PTCH1 , 1‐4 with cases of ACTB‐GLI1 fusion‐positive tumors showing a distinctive monomorphic round‐to‐epithelioid cell morphology and a nested to corded/trabecular pattern of growth, as well as an S100+/CD56+/SOX10−/SMA– immunophenotype 5 . Although few cases of this specific entity (herein termed ACTB‐GLI1 epithelioid mesenchymal neoplasm [EMN]) have been reported in the literature, most cases have occurred in the soft tissues of the limbs, trunk, and head and neck, with none previously reported occurring exclusively in the skin 1 …”
Section: Introductionmentioning
confidence: 99%